Effectiveness of Hoffman's Exercise in Postnatal Mothers With Grade 1 Inverted Nipples. (February 2023) - Thurkkada, Anju Philip; Rajasekharan Nair, Salini; Thomas, Sara; Sreelekha, Parvathy; Sanu, Soumya Kadakkuzha; Chandran, Parvathy R; Pillai Sreekanth, Gopinathan
Background: Breastfeeding provides perfect nutrition for infants. The inverted nipples in mothers make breastfeeding more challenging. Besides surgical approaches, non-pharmacological interventions are also gaining importance. Research Aim: To evaluate the effectiveness of Hoffman's exercise on breastfeeding among postnatal mothers with grade I inverted nipples. Method: A quantitative approach with a parallel arm randomized controlled trial was used in the study. Postnatal mothers were screened for inverted nipples using a pinch test. Participants with at least one inverted nipple (Grade 1) were randomly allocated into two groups: the experimental group (supported with Hoffman's exercise; n = 28, 50.9% ) and the control group (without Hoffman's exercise; n = 27, 49.1%). The pre-test data, including demographics, nipple length, and breastfeeding assessment, were collected. Breastfeeding assessment was evaluated using the Bristol Breastfeeding Assessment Tool (BBAT). On the 3rd day, the post-test data, including nipple length and Breastfeeding Assessment, were collected among the groups. Results: The BBAT assessment was significantly higher in the post-test compared to that of the pre-test in the participants provided with Hoffman's exercise. The nipple length was found to be higher in participants provided with Hoffman's exercise. Furthermore, the variables—including age, gravida, nipple problems, and delivery type—were not found to have any significant effect with either pre-test or post-test levels of breastfeeding. Conclusions: Hoffman's exercise was found to be an effective method to improve breastfeeding in Grade 1 nipple-inverted among post-natal mothers. This nipple exercise is inexpensive, easy to follow, and results in the successful initiation of breastfeeding. Clinical Trial Registry and Registration Number: CTRI/2019/05/019279, May 23, 2019 (retrospectively registered)